PENGELOLAAN OBYEK PARIWISATA MENGHADAPI POTENSI BENCANA DI BALIKPAPAN SEBAGAI PENYANGGA IBUKOTA NEGARA BARU - Fadhiil Ali Hakim; Joshua Banjarnahor; Risma Suryani Purwanto; Hayatul Khairul Rahmat; I Dewa Ketut Kerta Widana (NUSANTARA : Jurnal Ilmu Pengetahuan Sosial, 2020)
Balikpapan is a large city located in East Kalimantan Province. Balikpapan City is one of the tourist destination cities in East Kalimantan, because Balikpapan City has many tourism objects. However, besides the many tourism objects, Balikpapan City is also surrounded by potential disasters originating from the tourism object area. This study aims to analyze the readiness of tourism object managers in facing potential disasters in Balikpapan City. Analyzing the readiness of tourism object managers in facing potential disasters in Balikpapan City. This research uses a case study descriptive approach. This research is a research with a qualitative approach with a case study design. The data analysis used is rating based on existing laws and regulations and supported by existing theories as a reference for analyzing each readiness and knowledge variable. The results show that the level of readiness of the Balikpapan City Youth, Sports and Tourism Office is still not able to make tourism safe from disasters in anticipation of the planned relocation of the new national capital and Balikpapan as a buffer city for the new nation's capital. The implication of tourism for the Balikpapan community is that it has not been able to increase public knowledge of disasters because the Youth Sports and Tourism Office is still less significant in carrying out disaster activities in the tourism object environment.